2021
DOI: 10.3168/jds.2020-18503
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein gene expression and the oxidative phosphorylation pathway associated with feed efficiency and energy balance in dairy cattle

Abstract: Feed efficiency and energy balance are important traits underpinning profitability and environmental sustainability in animal production. They are complex traits, and our understanding of their underlying biology is currently limited. One measure of feed efficiency is residual feed intake (RFI), which is the difference between actual and predicted intake. Variation in RFI among individuals is attributable to the metabolic efficiency of energy utilization. High RFI (H_RFI) animals require more energy per unit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
(86 reference statements)
2
15
0
Order By: Relevance
“…Previously, direct effects of animal feed on oxidative phosphorylation (OXPHOS) pathway have been shown [65][66][67]. Our data clearly shows significant differences in the protein expression of the mitochondrial electron transport chain between the experimental diets used.…”
Section: Discussionsupporting
confidence: 49%
“…Previously, direct effects of animal feed on oxidative phosphorylation (OXPHOS) pathway have been shown [65][66][67]. Our data clearly shows significant differences in the protein expression of the mitochondrial electron transport chain between the experimental diets used.…”
Section: Discussionsupporting
confidence: 49%
“…Importantly, Eukaryotic translation initiation factor 3 subunit F was increased while Eukaryotic initiation factor 4A1 was decreased in four pathways of energy metabolism. Previous studies related to proteomic experiments have showed the relation between DAPs of FE and RFI 34 , 35 . However, this is the first report of AT tissue of mid lactation cows with an up-regulation of TF, EIF3F, MAP1LC3B and MT-ATP6 of low versus high RFI.…”
Section: Discussionmentioning
confidence: 96%
“…Dnajc2 gene, which was connected with the Atp8b2 gene, is thought to be an epigenetic factor (e.g., Aloia, Demajo, &Di Croce, 2015), andRamayo-Caldas et al (2019) reported that the expression level of DNAJC2 gene in gluteus medius muscle of Duroc pigs was different between high and low RFI groups. Significant terms for the genes in the network obtained using the DAVID included ones relating to mitochondrial function, such as "mmu00190: Oxidative phosphorylation" which were also reported as the important pathway for feed efficiency in several livestock species (e.g., Dorji et al, 2021;Fu et al, 2017;Yang, He, et al, 2020;Yang, Zhang, et al, 2020) (Table S1). The terms "mmu01100: Metabolic pathways", "mmu04714: Thermogenesis" and "GO:0005739 mitochondrion" were also significant.…”
Section: Possible Candidate Causal Genes For Oxygen Consumptionmentioning
confidence: 99%